PERSEPSI MASYARAKAT KELURAHAN TAWANGSARI TERHADAP KEBIJAKAN REKLAMASI PANTAI MARINA SEMARANG - Ahmadi Ade Iskandar; Susilo Utomo; Puji Astuti (Journal of Politic and Government Studies, 2016)
ABSTRACT Population growth in the city of Semarang from year to year more and more rapidly. As a result, the burden to be borne by the city of Semarang became increasingly severe. Infrastructure and municipal infrastructure, such as residential, industrial, public spaces, offices and business centers, inevitably be a demand that must be met by the local government. The rate of growth raises the problem of limited land in the city of Semarang. This has an impact on population density, which finally emerged seizure of land tenure. Therefore, attempts were made to obtain new land, such as by the expansion of the city made toward vacant lots and watery in a way to backfill / reclamation. This study aimed to perception of what are emerging from Village community Tawangsari against reclamation policy Marina Beach Semarang. This study uses a quantitative approach using survey research methods. Data collection methods using questionnaires then filled by the respondents, namely the Village community Tawangsari Semarang. The distribution of respondents was conducted using random sampling techniques. This means that all populations have the same opportunity to serve as the respondent. The findings of this study include that reclamation will be undertaken in the area of Marina Beach PT.IPU land reclamation will be used for new housing , office / shop , and several public facilities such as several schools from kindergarten level - childhood to higher education , as well as one hospital the new private sector will be built , but due to lack of socialization on the matter, many people who do not agree with their reclamation Beach Marina , besides that most people also believe that reclamation will have a negative impact on the environment Keywords: Public Perception, Public Policy, Reclamation